Pengaruh 2,4-D dan BAP Terhadap Multiplikasi Tunas Nanas (Ananas comosus L. Merr) Varietas Queen Bogor Secara in vitro - Fatimah Nursandi; Ratna Tri Widiastuti; Aulia Zakia; Frida Rahma Andini; Untung Santoso (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
The supply of Queen Bogor pineapple seeds is still done conventionally which is obtained only when the plant is ripe, in limited and small quantities, and takes a long time. The study aims to determine the effect of 2,4-D and BAP on the multiplication of shoots of Ananas comosus L. Merr variety Queen Bogor in vitro. This study used a randomized complete block design with two factors and one control. The first factor is the concentration of 2,4-D which consist of 2 levels (1 mg/L and 2 mg/L). The second factor is the concentration of BAP which consist of 3 levels (2 mg/L, 3 mg/L, and 4 mg/L). Data were analyzed using the orthogonal contrast at level of 5%. If there is a real influence, a further HSD (Honest Significant Difference) test is carried out at a level of 5%. The control compared to the 2,4-D + BAP treatment showed no significant effect on the number of callus, number of buds, number of leaves, explant height, callus explants, sprouting explants, and dead explants. By interaction or singly, 2,4-D and BAP had no significant effect on all observed variables. The factors causing the contamination are the presence of particles that enter the media and the use of the tool is still hot